1998
DOI: 10.1029/98je01634
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of the optical properties and stability of oxygen on Ganymede

Abstract: Abstract. We present measurements of the optical properties of solid 02 and O2:H20 films and on the stability of oxygen in water ice at different temperatures. The experiments are meant to test hypotheses for the location of condensed molecular oxygen in Ganymede. We find that oxygen is not retained in water ice at Ganymede's recorded surface temperatures and analyze current questions associated with the existence of oxygen in this Jovian moon. The results suggest that solid oxygen and possibly other condensed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 61 publications
(39 reference statements)
5
29
0
Order By: Relevance
“…Instead, they are redeposited and trapped in the surface ice in colder regions. The presence of molecular oxygen in the solid phase on the surface of Europa is itself a puzzle (Baragiola and Bahr, 1998;. Recently, Hand et al (2006) argued that mixed clathrates of O 2 -CO 2 -SO 2 could solve the trapping problem.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they are redeposited and trapped in the surface ice in colder regions. The presence of molecular oxygen in the solid phase on the surface of Europa is itself a puzzle (Baragiola and Bahr, 1998;. Recently, Hand et al (2006) argued that mixed clathrates of O 2 -CO 2 -SO 2 could solve the trapping problem.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination by trapped atmospheric O 2 or CO 2 was thought to be low but possibly was not. More recent experiments (Vidal et al 1997, Baragiola andBahr 1998) suggest varied but lower O 2 yields. Baragiola et al (1999) report only small upper limits for direct production of trapped O 2 within ice by 60 keV O + 2 (G O 2 < 5 × 10 −4 ) and 100 keV H + (G O 2 < 4 × 10 −5 ), but higher yields are possible (Johnson 1999).…”
Section: Fig 15mentioning
confidence: 99%
“…Also, studies of 02 absorption band shapes and positions in the red (around 600 nm) showed that 02 had to be in the form of a solid, not a liquid or gas [Baragiola and Bahr, 1998]. These spectroscopic laboratory data imply that solid 02 exists at temperatures much colder than the average temperatures of Ganymede's surface ice.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for atmospheres came mainly from stellar occultations [Carlson et al, 1973 Baragiola and Bahr [1998] on the grounds of laboratory results that showed that 02 could not be retained in water ice in sufficient amounts to produce the observed absorption bands in Ganymede. Also, studies of 02 absorption band shapes and positions in the red (around 600 nm) showed that 02 had to be in the form of a solid, not a liquid or gas [Baragiola and Bahr, 1998].…”
Section: Introductionmentioning
confidence: 99%